2008
DOI: 10.1103/physreve.77.061701
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a possible tetrahedratic phase in a bent-core liquid crystal

Abstract: An experimental study of the heat capacity, mass density, magnetic-field-induced optical birefringence, linewidth and intensity of scattered light, and the viscosities associated with nematic order parameter fluctuations and fluid flow has been performed on an achiral bent-core liquid crystal above its clearing point temperature. The measurements reveal a transition between two optically isotropic phases that is consistent with recent theoretical predictions of a "tetrahedratic" form of orientational order.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Recently, the experimental indication of stable T and N T phases was indeed reported [14], along with earlier discovery of the biaxial nematic phase [15,16].…”
mentioning
confidence: 69%
“…Recently, the experimental indication of stable T and N T phases was indeed reported [14], along with earlier discovery of the biaxial nematic phase [15,16].…”
mentioning
confidence: 69%
“…Mean-field theory of bent-core liquid crystals predicts a manifold of nematic-type phases (without positional order) including uniaxial, biaxial and tetrahedratic phases 2 . Unusual properties of the bent-core nematic phases of resorcinol derivatives, such as the formation of optically active domains, enhanced flexoelectric effect 3 and strong magneto-optical effects 4,5 have been reported. Recently, the appearance of weakly first order nematic-nematic transitions and the identification of a novel nematic phase have been reported for cyanobiphenyl based odd methylene linked dimers (CBnCB) [6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, experimental studies of the nematic phase of bent-core LCs have reported a host of interesting properties, including: giant flexoelectricity [1]; a significant Kerr effect [2]; induced [3] and spontaneous [4,5] biaxial orientational order; unusually large viscosity to elasticity ratios [6,7] and flow viscosity [8]; new electro-convection behavior [9]; and indications of exotic orientationally ordered phases such as a tetrahedratic phase in the vicinity of the isotropic-nematic transition [10]. Meanwhile, theoretical investigations [11] of ordering in bent-core nematics (BCNs) have predicted the occurrence of spontaneously chiral and even polar nematic phases.…”
mentioning
confidence: 99%